Treatment of pediatric burn patient having glucose-6-phosphate dehydrogenase deficiency - Vijay Y Bhatia; Sankit D Shah; Harshil Y Ravalji; Deepa Banker (Wolters Kluwer Medknow Publications, 2016)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common red cell enzymopathy found in humans. It clearly has an X-linked recessive inheritance with its prevalence varying from 0% to 27% in a different caste, ethnic, and linguistic groups. This deficiency may result in hemolytic anemia during stress, infection, and use of certain drugs. The use of topical silver sulfadiazine can produce hemolysis in patients having G6PD deficiency. Here, we describe one case successfully treated of pediatric burn of 25% of body surface area who was a known case of G6PD deficiency.